Housing costs and family formation: Empirical evidence - Lindsay Flynn (Luxembourg Income Study (LIS), 2013)
What institutional configurations influence fertility patterns across countries? While family policies feature prominently in previous explanations, this article highlights the importance of housing in shaping family formation decisions. Housing costs, determined by state and market factors, directly compete with spending on children, prompting tradeoffs between the two. Housing further influences fertility by shaping transition decisions into parenthood, which in turn alter fertility behavior. This article provides the logic and empirical evidence linking housing to fertility both directly and indirectly. Direct links are examined through a Poisson regression model. Indirect links are tested through sets of bivariate statistics. Austria, Germany, France, and Italy serve as the primary test cases, with reference to other rich OECD countries. The findings suggest that the literature suffers from omitted variable bias: to understand fertility patterns we must broaden our coverage of institutional variables to include housing.
Keywords: 330; Fertilität; Familienplanung; Wohnungsversorgung; Statistische Verteilung; Deutschland; Österreich; Frankreich; Italien; OECD-Staaten